Оцінка наукової спадщини Миколи Костомарова в українській зарубіжній історіографії (1945-1991) - Ясь, О. (Історіографічні дослідження в Україні, 1998)
The article shows the process of formation of evaluating criteria in relation to the scientific legacy of Mykola Kostomarov, a well-known Russian and Ukrainian historian, in Ukrainian foreign historiography (1945-1991) and in particular, the influence of studies a review of the most important works dealing with the description, interpretation and evaluation of M.Kostomarov’s creative achievements.